Synthesis and enzymatic recycling of sugar-based bio-polyurethane foam. (15th May 2022) - Jeong, Jisu; Hong, Younggi; Lee, Min Wook; Goh, Munju
Graphical abstract: Highlights: Polyurethane foam (PUF) was successfully prepared by sugar with polyisocyanate. PUF was decomposed and recycled by an enzymatic reaction in water using invertase. The product of enzymatic decomposition of PUF could be recovered and reused as PUF. Abstract: Polyurethane foam (PUF) was prepared by reacting sugar with polyisocyanate and blowing using CO2 formed by reacting polyisocyanate with water. The optimum foaming rate of 840% was obtained at 15 wt% of sugar, and the synthesis and cellular structure of polyurethane were confirmed from Fourier-transform infrared (FT-IR) spectra and scanning electron microscopy (SEM) images. The apparent density and thermal conductivity of the optimized PUF were 0.114 – 0.126 g/mL and 0.049 – 0.053 W/(mK), respectively. At 15 wt% of sugar, the normalized compressive strength of PUF was 17.68 MPa/(g/mL) at 70% strain. PUF was degradable and recyclable by an enzymatic reaction in water using invertase. The degradation reactions using invertases were kinetically analysed. Furthermore, the product of enzymatic decomposition of PUF could be recovered and reused as PUF. This study demonstrated the possibility of synthesizing eco-friendly polymers using sugar and reusing them by enzymatic green recycling.